SUDDEN CHILDREN DEATH SYNDROME (SCDS) AS WELL AS SUDDEN INFANT DEATH SYNDROME (SIDS) - Юрий Иванович Ровда; Елена Михайловна Зеленина; Наталья Николаевна Миняйлова; Наталья Петровна Крекова (The Publishing House Medicine and Enlightenment, 2018)
The review gives the definition for the syndrome of sudden (and unexpected) death in children (including infants), its prevalence, likely causes and mechanisms of development. It also shows criteria for diagnosis of the diseases that might be symptoms free for a long time, but nevertheless there may be a sudden fatal outcome. The measures to prevent sudden infant death in children (including infants) as well as the best emergency care in case of premorbid SIDS or life-threatening condition are suggested.